2015
DOI: 10.1017/brimp.2015.16
|View full text |Cite
|
Sign up to set email alerts
|

Towards Measuring Community Understanding of Traumatic Brain Injury: The Structure and Potential Utility of the Head Injury Knowledge Scale

Abstract: Background and aims: International research has shown the public hold various misconceptions about traumatic brain injury (TBI). Yet, relatively little has been done towards developing appropriate measures of public knowledge of TBI. The Head Injury Knowledge Scale (HIKS, Ono, Ownsworth, & Walters, 2011) is a newly developed measure of misconceptions and expectations about the effects of TBI. Additional investigation of its psychometric properties appeared warranted. The aims of this further preliminary st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Notably, the Cronbach's alpha values for the two subscales improved: overgeneralisation α = .84, and minimisationα = .81. CFA also demonstrated a good fit to the original twodimensional model developed by Ono et al (26), although a moderate co-variance was found between the factors (43).…”
Section: Other Psychometric Considerationsmentioning
confidence: 71%
See 1 more Smart Citation
“…Notably, the Cronbach's alpha values for the two subscales improved: overgeneralisation α = .84, and minimisationα = .81. CFA also demonstrated a good fit to the original twodimensional model developed by Ono et al (26), although a moderate co-variance was found between the factors (43).…”
Section: Other Psychometric Considerationsmentioning
confidence: 71%
“…A negative correlation was also found between the two sub-scales, giving weight to the claim that they represent two opposing dimensions (26). In its original format, a true-false response format was adopted; however, to carry out confirmatory factor analysis (CFA) and improve levels of internal consistency, a 4-point scale was subsequently adopted (43). Notably, the Cronbach's alpha values for the two subscales improved: overgeneralisation α = .84, and minimisationα = .81.…”
Section: Other Psychometric Considerationsmentioning
confidence: 99%